Report of the Working Group for Forlmulation of 5th Five year Plan on Community Development & Panchayati Raj India Min. of Agriculture - Planning Commission (Planning Commission, 1972)
The Community Development Programme was launched in 1952. The basic objective of the programme was to secure the fullest development of the material and human resources of rural areas, on an area basis and develop local leadership and self governing institutions and thereby raise the rural community to higher levels of living with the active participation, and, as much as possible, on the initative of the peoples themselves. With the country-wide coverage as its scope and integrated development of rural areas as its anoroach, the experiment in the country is an instance' of the "integrative" tyne of Community Development
Government of India Ministry of Agriculture
Government of India Ministry of Agriculture